Stratification of Diversity and Activity of Methanogenic and Methanotrophic Microorganisms in a Nitrogen-Fertilized Italian Paddy Soil - Vaksmaa, Annika; van Alen, Theo A.; Ettwig, Katharina F.; Lupotto, Elisabetta; Valè, Giampiero; Jetten, Mike S. M.; Lüke, Claudia (Frontiers in Microbiology, 2017)
Paddy fields are important ecosystems, as rice is the primary food source for about half of the world’s population. Paddy fields are impacted by nitrogen fertilization and are a major anthropogenic source of methane. Microbial diversity and methane metabolism were investigated in the upper 60cm of a paddy soil by qPCR, 16S rRNA gene amplicon sequencing and anoxic 13C-CH4 turnover with a suite of electron acceptors. The bacterial community consisted mainly of Acidobacteria, Chloroflexi, Proteobacteria, Planctomycetes and Actinobacteria. Among archaea, Euryarchaeota and Bathyarchaeota dominated over Thaumarchaeota in the upper 30cm of the soil. Bathyarchaeota constituted up to 45% of the total archaeal reads in the top 5cm. In the methanogenic community, Methanosaeta were generally more abundant than the versatile Methanosarcina. The measured maximum methane production rate was 444 nmol gdwh-1, and the maximum rates of nitrate-, nitrite- and iron-dependent anaerobic oxidation of methane (AOM) were 57 nmol, 55 nmol and 56 nmol gdwh-1, respectively, at different depths. qPCR revealed a higher abundance of ‘Candidatus Methanoperedens nitroreducens’ than methanotrophic NC10 phylum bacteria at all depths, except at 60cm. These results demonstrate that there is substantial potential for anaerobic oxidation of methane in fertilized paddy fields, with ‘Candidatus Methanoperedens nitroreducens’ archaea as a potential important contributor.